African experiences of laparoscopic hysterectomy about a continuous series of 52 cases by the same practitioner: indications, surgical procedures and complications - Koffi, Koffi Abdoul; Aka, Kacou Edele; Fomba, Minata; Seni, Konan; Horo, Apollinaire; Kone, Mamourou (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Laparoscopy is a modern surgical technique that began in 1940 with Raoul Palmer. The present study aimed to analyse the results of a fifty-two-laparoscopic hysterectomy performed. Methods: A prospective study over a period of seven years from 1st January 2010 to 31st December 2015. A total of 52 patients who underwent a laparoscopic hysterectomy were recruited at the teaching hospital of Yopougon-Abidjan. Results: The mean age was 50.2 years (±3.9 years) (36-62 years). The average parity was 3. Few patients had undergone anterior pelvic surgery for either myomectomy or caesarean section. Uterine fibroid was the major surgical indication with a rate of 61.54%. The average size of the uterus was 12 cm (8-18 cm). Total hysterectomies type II and III with or without adnexectomy were essentially performed with rates of 28.85% and 32.69%, respectively. Sometimes it was associated with a lymphadenectomy or a colpo-suspension. The average length of a hysterectomy is 170 minutes (87-385 minutes). Four cases of laparo-conversions have been noted. Blood loss was approximately 95 ml (±12 ml) with a maximum of 300 ml. The complications were mainly two digestive wounds and a bladder fistula. The average length of hospital stay is three days apart from any complication. Conclusions: The laparoscopic approach is less painful, is associated with less blood loss, shorter hospital stay, faster recovery, fewer complications, and better care. A training period of surgeons associated with the equipment of the health structures is necessary to popularize this procedure surgical.